New record of the genus Caputanurina Lee, 1983 (Collembola: Neanuridae) from China, with description of a new species - Wu, Donghui; Yin, Wenying (Zootaxa, 2007)
Caputanurina sinensis, a new species from Anshan city, Liaoning Province, Northeast China, is described in the present paper. A key to the species of the genus Caputanurina is provided.